Inhibition of Sirtuin 2 with Sulfobenzoic Acid Derivative AK1 is Non-Toxic and Potentially Neuroprotective in a Mouse Model of Frontotemporal Dementia - Spires-Jones, Tara L.; Fox, Leora M.; Rozkalne, Anete; Pitstick, Rose; Carlson, George A.; Kazantsev, Aleksey G. (Frontiers in Pharmacology, 2012)
Tauopathies including tau-associated Frontotemporal dementia and Alzheimer’s disease are characterized pathologically by the formation of tau-containing neurofibrillary aggregates and neuronal loss, which contribute to cognitive decline. There are currently no effective treatments to prevent or slow this neural systems failure. The rTg4510 mouse model, which expresses a mutant form of the tau protein associated with frontotemporal dementia with Parkinsonism-17, undergoes dramatic hippocampal and cortical neuronal loss making it an ideal model to study treatments for FTD-related neuronal loss. Sirtuins are a family of proteins involved in cell survival that have the potential to modulate neuronal loss in neurodegenerative disorders. Here we tested the hypothesis that sirtuin 2 (SIRT2) inhibition would be non-toxic and prevent neurodegeneration in rTg4510 brain. In this study we delivered SIRT2 inhibitor AK1 directly to the hippocampus with an osmotic minipump and confirmed that it reached the target region both with histological assessment of delivery of a dye and with a pharmacodynamic marker, ABCA1 transcription, which was upregulated with AK1 treatment. AK1 treatment was found to be safe in wild-type mice and in the rTg4510 mouse model, and further, it provided some neuroprotection in the rTg4510 hippocampal circuitry. This study provides proof-of-concept for therapeutic benefits of SIRT2 inhibitors in both tau-associated FTD and Alzheimer’s disease, and suggests that development of potent, brain permeable SIRT2 inhibitors is warranted.